2021
DOI: 10.3390/su131910709
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Promising Smart Farm Technologies and Development of Technology Roadmap Using Patent Map Analysis

Abstract: In this study, we suggest methodologies for identifying promising and vacant technologies on smart farms by analyzing patent information. Additionally, a technology roadmap for smart farms is suggested using network analysis. The database of patents related to smart farms was extracted from the United States Patent and Trademark Office (USPTO) by keyword search, and valid patents data was selected and clustered using the Latent Dirichlet Allocation (LDA) algorithm. We also conducted the technical importance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…According to the previous research, the smart industry was classified into IT manufacturing (e.g., computer, and electronic and electricity equipment), IT service (e.g., communication, S/W and broadcast) and knowledge service (e.g., education, health and welfare, culture and sports). In order to define the smart industry, this study identified the main technologies applied to the smart city through the smart-x case such as smart car [28], smart building [29], smart farm [30] and smart factory [31]. This smart-x industry expects production to grow exponentially by 2026 [32][33][34][35].…”
Section: Smart City Industrymentioning
confidence: 99%
“…According to the previous research, the smart industry was classified into IT manufacturing (e.g., computer, and electronic and electricity equipment), IT service (e.g., communication, S/W and broadcast) and knowledge service (e.g., education, health and welfare, culture and sports). In order to define the smart industry, this study identified the main technologies applied to the smart city through the smart-x case such as smart car [28], smart building [29], smart farm [30] and smart factory [31]. This smart-x industry expects production to grow exponentially by 2026 [32][33][34][35].…”
Section: Smart City Industrymentioning
confidence: 99%
“…1 In the first quadrant, both TAI and TII indicators are high, which is defined as high level, and 2 in the second and 3 third quadrants, one of the TAI and TII indicators is high and is defined as medium level. Finally, 4 the fourth quadrant is defined as the low level where all indicators are low [108,109].…”
Section: Technology Level Assessmentmentioning
confidence: 99%
“…○ 1 In the first quadrant, both TAI and TII indicators are h high level, and ○ 2 in the second and ○ 3 third quadrants, one o tors is high and is defined as medium level. Finally, ○ 4 the fourt the low level where all indicators are low [108,109]. Trend analysis aims to predict the future of technology.…”
Section: Technology Level Assessmentmentioning
confidence: 99%
“…Qualitative evaluation is a method of evaluating the relative level of technology for information on patent data [70]. We can identify the technology level by applying the technology mapping analysis [71]. In addition, through quantitative evaluation, the indicator of centrality and time series were extracted from each detailed IPC technology area, and the results of the analysis were confirmed through social network analysis and time series analysis [72,73].…”
Section: Technology Level Evaluation Of Ipcmentioning
confidence: 99%